(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2024)
Migraine is a chronic disease that accounts for 15% worldwide. It is one of the most important causes of disability among women under 50 years of age. Migraines cause difficulties in socio-economic and everyday life. Chronic migraine causes a sharp decrease in the quality of life of the patient, leading to an increase in the cost of the disease, both directly and indirectly. In order to prevent migraine-related disability, today there are ways to prevent disease attacks and prevent seizures. Chronic migraines usually occur after episodic migraines. This has been confirmed in a large number of studies. Immunological mechanisms in migraines are studied as far as hanuz